2022
DOI: 10.3390/rs14020331
|View full text |Cite
|
Sign up to set email alerts
|

Combining Spectral and Texture Features of UAS-Based Multispectral Images for Maize Leaf Area Index Estimation

Abstract: The leaf area index (LAI) is of great significance for crop growth monitoring. Recently, unmanned aerial systems (UASs) have experienced rapid development and can provide critical data support for crop LAI monitoring. This study investigates the effects of combining spectral and texture features extracted from UAS multispectral imagery on maize LAI estimation. Multispectral images and in situ maize LAI were collected from test sites in Tongshan, Xuzhou, Jiangsu Province, China. The spectral and texture feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 57 publications
5
17
0
2
Order By: Relevance
“…This study supports the notion that successful feature selection approaches aid in identifying the most important features or aspects that contributed to crop yield prediction. Our result was consistent with the study of (Fashoto et al 2021;Zhang et al 2022), who adopted backward elimination as a feature selection technique in estimating yield. The selection revealed that rainfall precipitation derived from CHIRPS satellite, some VIs such as EVI, GCVI, GNDVI, MSAVI, NDVI, SAVI, age and leaf N were found to be the most significant predictors (P< 0.05) in the yield prediction.…”
Section: Correlation Between Attributes and Yield With Backward Elimi...supporting
confidence: 92%
“…This study supports the notion that successful feature selection approaches aid in identifying the most important features or aspects that contributed to crop yield prediction. Our result was consistent with the study of (Fashoto et al 2021;Zhang et al 2022), who adopted backward elimination as a feature selection technique in estimating yield. The selection revealed that rainfall precipitation derived from CHIRPS satellite, some VIs such as EVI, GCVI, GNDVI, MSAVI, NDVI, SAVI, age and leaf N were found to be the most significant predictors (P< 0.05) in the yield prediction.…”
Section: Correlation Between Attributes and Yield With Backward Elimi...supporting
confidence: 92%
“… Zhou et al (2021) used drones to diagnose water stress in winter wheat. Zhang et al (2022) also introduced the combination of texture features and vegetation index to improve the model accuracy in the study of maize leaf area index estimation by UAV. Combined with the results of this study, it is feasible to improve the accuracy of cotton yield monitoring model by combining vegetation index and texture feature.…”
Section: Discussionmentioning
confidence: 99%
“…Stepwise MLR (SMLR) is a modeling method that eliminates covariance by removing unnecessary independent variables through AIC value minimization iterations and selecting significant independent variables to obtain the optimal regression model. The SMLR model has simple logic and clear physical meaning of the independent variables, indicating that it is an interpretable machine learning model ( Yu et al., 2016 ; Han et al., 2019 ; Zhang et al., 2022 ). Partial least-squares regression (PLSR) is one of the widely used machine learning methods that combines the basic functions of MLR, canonical correlation analysis, and principal component analysis.…”
Section: Methodsmentioning
confidence: 99%